2016
DOI: 10.1093/jamia/ocv203
|View full text |Cite
|
Sign up to set email alerts
|

Describing the evolution of mobile technology usage for Latino patients and comparing findings to national mHealth estimates

Abstract: Published national estimates do not accurately reflect the mobile technology use of Latino patients served by our public safety-net facility. The difference is greater for older, less educated patients with chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Thus, we aimed, as best possible and while maintaining an ethical research approach, to simulate realworld conditions in this study. Second, because the Beiwe application runs on both Android and Apple smartphones, we did not exclude any subjects based on the type of phone they owned, which is important as phone may be a proxy for socioeconomic status [29,30], which is known to be associated with both overall health and the type of health care that is available to individuals [31,32]. Third, given that the Beiwe platform is open source, others will be able to conduct similar studies and can replicate or disprove our results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we aimed, as best possible and while maintaining an ethical research approach, to simulate realworld conditions in this study. Second, because the Beiwe application runs on both Android and Apple smartphones, we did not exclude any subjects based on the type of phone they owned, which is important as phone may be a proxy for socioeconomic status [29,30], which is known to be associated with both overall health and the type of health care that is available to individuals [31,32]. Third, given that the Beiwe platform is open source, others will be able to conduct similar studies and can replicate or disprove our results.…”
Section: Discussionmentioning
confidence: 99%
“…While most were positive to the idea of using an app to manage GDM, they were sometimes discouraged by the technical issues. A cross-sectional survey on mHealth use among Latino patients with diabetes found that the lack of operability between the smartphone app and other devices could serve as a barrier to using the app (Arora et al, 2016). In the same study, the perceived lack of additional benefits was also an important barrier (Arora et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey on mHealth use among Latino patients with diabetes found that the lack of operability between the smartphone app and other devices could serve as a barrier to using the app (Arora et al, 2016). In the same study, the perceived lack of additional benefits was also an important barrier (Arora et al, 2016). In our study, many women no longer seemed to see the benefits of using the app when the automatic transfer of the blood glucose values didn't work.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the Android platform is more common in some racial and/or ethnic groups, thus the availability of an Android version of AHA (facilitated by the open source ResearchKit framework) could capture a more representative sampling of the general population. Other nuances, such as a propensity to text rather than use apps in low-income Hispanic communities should be considered in attaining diverse participation in mobile health research 13,14 .…”
Section: Discussionmentioning
confidence: 99%